Predawn and high intensity application of supplemental blue light decreases the quantum yield of PSII and enhances the amount of phenolic acids, flavonoids, and pigments in Lactuca sativa - Ouzounis, Theoharis; Razi Parjikolaei, Behnaz; Fretté, Xavier; Rosenqvist, Eva; Ottosen, Carl-Otto (Frontiers in Plant Science, 2015)
To evaluate the effect of blue light intensity and timing, two cultivars of lettuce [Lactuca sativa cv. ’Batavia’ (green) and cv. ‘Lollo Rossa’ (red)] were grown in a greenhouse compartment in late winter under natural light and supplemental high pressure sodium (SON-T) lamps yielding 90 (±10) µmol m-2 s-1 for up to 20 hr, but never between 17:00 and 21:00. The temperature in the greenhouse compartments was 22/11°C day/night, respectively. The five light-emitting diode (LED) light treatments were Control (no blue addition), 1B 06-08 (Blue light at 45 µmol m-2 s-1 from 06:00 to 08:00), 1B 21-08 (Blue light at 45 µmol m-2 s-1 from 21:00 to 08:00), 2B 17-19 (Blue at 80 µmol m-2 s-1 from 17:00 to 19:00), and (1B 17-19) Blue at 45 µmol m-2 s-1from 17:00 to 19:00. Total fresh and dry weight was not affected with additional blue light; however, plants treated with additional blue light were more compact. The stomatal conductance in the green lettuce cultivar was higher for all treatments with blue light compared to the Control. Photosynthetic yields measured with chlorophyll fluorescence showed different response between the cultivars; in red lettuce, the quantum yield of PSII decreased and the yield of non-photochemical quenching increased with increasing blue light, whereas in green lettuce no difference was observed. Quantification of secondary metabolites showed that all four treatments with additional blue light had higher amount of pigments, phenolic acids, and flavonoids compared to the Control. The effect was more prominent in red lettuce, highlighting that the results vary among treatments and compounds. Our results indicate that not only high light level triggers photoprotective heat dissipation in the plant, but also the specific spectral composition of the light itself at low intensities. However, these plant responses to light are cultivar dependent.